2016
DOI: 10.1142/s0217984916300052
|View full text |Cite
|
Sign up to set email alerts
|

All-optical spin switching: A new frontier in femtomagnetism — A short review and a simple theory

Abstract: Using an ultrafast laser pulse to manipulate the spin degree of freedom has broad technological appeal. It allows one to control the spin dynamics on a femtosecond time scale. The discipline, commonly called femtomagnetism, started with the pioneering experiment by Beaurepaire and coworkers in 1996, who showed subpicosecond demagnetization occurs in magnetic Ni thin films. This finding has motivated extensive research worldwide. All-optical helicity-dependent spin switching (AOS) represents a new frontier in f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 118 publications
1
47
1
Order By: Relevance
“…To start with, we note that all-optical spin reversal is an optical process and must follow the dipole selection rule. Consider a laser field propagating along the −z axis toward a sample surface [28,32] (see Fig. 1),…”
Section: A Optical Selection Rulementioning
confidence: 99%
See 1 more Smart Citation
“…To start with, we note that all-optical spin reversal is an optical process and must follow the dipole selection rule. Consider a laser field propagating along the −z axis toward a sample surface [28,32] (see Fig. 1),…”
Section: A Optical Selection Rulementioning
confidence: 99%
“…Over the years, the explanation progresses from the inverse Faraday effect [10,19], Raman scattering [20,21], magnetic circular dichroism [22], pure heating [16], and sublattice spin exchange [23], to ultrafast exchange scattering [24], with new theories emerging in ferromagnets [25][26][27]. This raises a serious question whether a big picture is missing from the existing theories [28]. Furthermore, no theory ever addresses a design protocol for future photospintronic devices based on AOS technology [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most simulations have been phenomenological, 6 where laser fields are treated as an effective magnetic field. 13 Ostler et al 6 and Mentink et al 53 showed that in GdFeCo, HID-AOS and HD-AOS depend on the laser intensity (electric field squared), not the field helicity. As shown in our recent study, 54 caution must be taken if the system has two spin sublattices.…”
Section: Dynamical Simulationmentioning
confidence: 99%
“…As discussed above, the majority of theoretical research has been phenomenological. 13 This calls for a systematic experimental investigation by tuning both system-and laser-specific parameters. Before one can pin down the origin of AOS, it is necessary to develop a many-to-one correspondence between the proposed mechanisms (see Table 1) and more fundamental interactions.…”
Section: Simple Theory For All-optical Switchingmentioning
confidence: 99%
“…In our model, we add a twist by replacing the tight-binding term by a real-space kinetic energy and potential energy term, so we can easily include one extra term, spin-orbit interaction. With these conditions in mind, we have the Hamiltonian as [37][38][39][40][41],…”
Section: Theoretical Formalismmentioning
confidence: 99%